2021
DOI: 10.1097/md.0000000000025843
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia and jaundice in newborns with pituitary stalk interruption syndrome

Abstract: Pituitary stalk interruption syndrome (PSIS) is a rare disease associated with either isolated growth hormone deficiency (GHD) or combined pituitary hormone deficiency (CPHD). In older children and adults, most patients experience short stature or hypogonadism. Neonatal PSIS is extremely rare and is difficult to recognize due to absence of dwarfism. However, when this condition occurs in newborns, it is often life-threatening. Here, we collected patients with neonatal PSIS to clarify its characteristics to imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
5
0
2
Order By: Relevance
“…Hypoglycemia, jaundice, short stature, and central obesity were the most clinical findings in these boys with a micropenis (Wang et al, 2021). Our study showed that thyrotropin was normal in boys without these clinical features.…”
Section: Tsh Assaysupporting
confidence: 46%
See 1 more Smart Citation
“…Hypoglycemia, jaundice, short stature, and central obesity were the most clinical findings in these boys with a micropenis (Wang et al, 2021). Our study showed that thyrotropin was normal in boys without these clinical features.…”
Section: Tsh Assaysupporting
confidence: 46%
“…The most hormonal abnormalities in children with hypopituitarism were hypothyroidism (54%) and growth hormone disturbance (56%). Hypoglycemia, jaundice, short stature, and central obesity were the most clinical findings in these boys with a micropenis (Wang et al, 2021). Our study showed that thyrotropin was normal in boys without these clinical features.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the diseases in the group of metabolic disorders as well as the cardiovascular and chromosomal disorders are known to have malformations related to the disease aetiology regardless of the presence of cholestasis. [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93] The details can be seen in Table 2B and Table S5.…”
Section: Malformationsmentioning
confidence: 99%
“…Clinical manifestations vary based on the extent of pituitary stalk damage, primarily determined by the type and degree of hormone defciency. Symptoms may include growth retardation, hypogonadotropic hypogonadism, hypoglycemia, hyponatremia, and central hypothyroidism [4,5]. Most patients seek medical attention for growth retardation and hypogonadotropic hypogonadism, but some of them do not exhibit short stature [4,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%